Lysosomal interplay between ubiquitination and phosphorylation regulates chaperone-mediated autophagy - Rakshit, Moumita (2017)
Chaperone-mediated autophagy (CMA) is a selective autophagic pathway that degrades soluble cytosolic proteins. It utilizes a cascade of chaperones and co-chaperones to recognize and deliver the substrates to the lysosome for degradation. Basal CMA operates in all mammalian cells in order to maintain protein homeostasis and quality control as well as performing specific functions in some cells like kidney cell growth, neuronal survival, antigen presentation and selective degradation of specific transcription factors or metabolic enzymes. CMA is induced upon stress and performs various cellular functions like recycling of raw materials under nutrient starvation, protection against oxidative stress, toxic stress and hypoxic stress. The rate limiting step in CMA is substrate binding to the lysosomal receptor lysosome-associated membrane protein-2A (LAMP-2A) followed by formation of the multimeric LAMP-2A translocation complex. It has been reported that the mTORC2/Akt1/PHLPP1 pathway regulates CMA activity by influencing the formation the LAMP-2A translocation complex. CMA is impaired during aging resulting in metabolic failure and various neurodegenerative disorders. Thus there is tremendous interest in understanding the regulation and deriving ways to regulate CMA function to harness pathological benefits. Certain evidences suggest the role of ubiquitination in CMA pathway. For instance, rat liver lysosomes depleted of CMA promoted accumulation of ubiquitin-positive aggregates, K63-ubiquitination is necessary for CMA degradation of HIF-1α and accumulation of K48 ubiquitinated protein in CMA-abolished cells, however, the exact role of ubiquitination in targeting substrates to CMA pathway remains unclear. The current study has shown the novel role of the ubiquitin system in CMA regulation by uncovering the presence of ubiquitin and a plethora of ubiquitin modifying enzymes associated with the subgroup of lysosomes specifically dedicated to perform CMA (henceforth known as CMA-active lysosomes). Based on these observations, this project aims to understand the potential modulatory role of selected lysosome associated ubiquitin modifying enzymes- E4 ligase carboxyl-terminus of Hsp70 interacting protein (CHIP) and the deubiquitinating enzyme ubiquitin C-terminal hydrolase - L1 (UCH-L1) in different aspects of CMA pathway. CHIP and UCH-L1 have been previously implicated in regulating the levels of Protein kinase B (Akt) and PH Domain and Leucine Rich Repeat Protein Phosphatase 1 (PHLPP1), but it is not known whether this function of CHIP and UCH-L1 can regulate CMA activity. Addressing this query, the present study has revealed that CHIP is an activator of CMA while UCH-L1 inhibits CMA by regulation of Akt1 and PHLPP1 levels. Knockdown studies revealed that depletion of CHIP leads to changes in lysosomal levels of ubiquitin, CMA associated chaperones as well as accumulation of pAkt1 accompanied by a decrease in levels of PHLPP1. CHIP helps in ubiquitination of pAkt1 leading to its proteasomal degradation. In the absence of CHIP, pAkt1 accumulates which leads to downstream destabilization of LAMP-2A translocation complex resulting in CMA inhibition. In contrast, knockdown studies on UCH-L1 indicate that depletion of UCH-L1 leads to accumulation of PHLPP1 accompanied by a reduction in pAkt1 levels in the lysosomes leading to stabilization of the LAMP-2A complex and promoting CMA activity. Effectively, CHIP and UCH-L1 regulate CMA activity by manipulation of the mTOR/Akt1/PHLPP1 pathway. Subsequently, it was observed that CHIP regulates the levels of UCH-L1 at the lysosomes by ubiquitination and lysosomal degradation of UCH-L1. Thus, the two enzymes operate in the same pathway; their activities being interconnected. The evidence that the ubiquitin modifying enzymes associate with CMA-active lysosomes and regulate CMA activity could indicate a possible crosstalk between the ubiquitin proteasome system (UPS) and CMA pathway. In the current study, it was observed that upon inhibition of the proteasomal pathway, CHIP localized at the lysosomes, thus reducing lysosomal levels of UCH-L1, pAkt1 and increasing levels of PHLPP1. This could indicate a rise in CMA activity under proteasomal stress. Thus in this study, a novel mechanism of CHIP-mediated crosstalk between the UPS and CMA pathways upon conditions of proteasomal stress has been identified. This study has been advantageous in understanding the intricate connection between ubiquitination and phosphorylation pathways regulating CMA activity and can be exploited in developing therapeutic benefits by cell type specific studies as UCH-L1 is highly abundant in brain. The current study also provides an insight in understanding the crosstalk between the UPS and CMA degradation pathways both of which are implicated in various neurodegenerative diseases.